Recycling Plastic Waste Into Something That Has A Selling Value - Achmad Zulfikar Siregar; Komala Dewi; Fauziah Nur Hutauruk (SEAN Institute, 2023)
Plastic waste is the most waste in every country, including Indonesia. In Indonesia alone, the use of plastic reaches thousands of tons every day, the high rate of plastic use has been made by Indonesia, one of the countries that produces the most plastic waste in the world. this should be of particular concern to every community in order to reduce the plastic waste. the community can utilize the plastic waste into something that has selling value. With the open mind of every community about this, the community can open business opportunities with this plastic waste. In addition to opening business opportunities, the use of plastic waste will slowly reduce the amount of plastic waste around the community. This research method uses the library method. research, namely through the first 3 stages of recording, integrating and analyzing.